3 Kv Conveyor Motor Maintenance At PT. PLN Nusantara Power Up Paiton Units 1 And 2 - Ajub Ajulian ZM; Karnoto; Winardi, Bambang (Journal of International Multidisciplinary Research, 2024)
Preventive Maintenance, Predictive Maintenance, Corrective Maintenance in induction motor 3 phase is one of the equipment that is highly used to support the various processes. In general, induction motors are used to rotate pumps, blowers or compressors. Maintenance is a combination of various action taken to maintain an asset and repairs that is always in a ready to use condition to carry out productivity effectively and efficiently in accordance with standards. To improve the performance of the generator in the PLTU, and maintain the working performance of the motor routine maintenance needs to be carried out. Motor maintenance is one of the most important things to increase the reliability of the production process in an industry. In various industrial activities which are full of exciting processes, motor motors are one of the equipment or tools that are highly used to support these various processes. In large industries, induction motor, are the main control for driving other equipment.